ANFIS-based MPPT Controller Design on Boost Converter to Improve Photovoltaic System Performance - Nrartha, I Made Ari; Alfian, Muhammad Rolan; Zubaidah, Teti (Jurusan Teknik Elektro Fakultas Teknik Universitas Mataram, 2022)
The efficiency of the photovoltaic system is very low ranging from 9-17% in areas with low irradiation while the investment costs are quite high. In addition, the power output of the photovoltaic system is highly volatile due to changes in irradiation due to weather and cloud movement, and temperature change. This research proposes the MPPT method based on ANFIS in the photovoltaic system for transient behavior analysis and system efficiency improvement. The results of the proposed method were compared with the MPPT Perthub & Observe (P&O) method. Each MPPT method was applied to a boost converter connected to a photovoltaic module with a capacity of 150 Wp to adjust the duty cycle using Simulink simulation in MATLAB. The irradiation and temperature data for 3 consecutive days were from Saturday to Monday, September 4 to 6, 2021. The simulation results show that the transient time of ANFIS MPPT is 6.23 times faster than that of P&O MPPT. The efficiency of ANFIS-based MPPT is higher than MPPT P&O. At 917.3 W/m2 of irradiation, the output power of the boost converters are 132.09, and 111.69 Watt for the ANFIS-based MPPT controller, and the P&O method MPPT, respectively.